2017
DOI: 10.1080/13510002.2017.1365224
|View full text |Cite
|
Sign up to set email alerts
|

Galangin, a natural flavonoid reduces mitochondrial oxidative damage in streptozotocin-induced diabetic rats

Abstract: We designed this study to observe the effect of galangin on damaged mitochondria in the liver of diabetic rats. Methods: Male albino Wistar rats were made diabetic by injecting streptozotocin (STZ) intraperitoneally (40 mg kg −1 body weight (BW)). Galangin (8 mg kg −1 BW) or glibenclamide (600 µg kg −1 BW) was given orally daily once for 45 days to both healthy and diabetic rats. Results: Diabetic rats showed significant (P < 0.05) increase in liver mitochondrial oxidant [Thiobarbituric acid reactive substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…The level of these enzymes in the red gastrocnemius was determined as described previously . According to the manufacturer's instructions, the levels of superoxide malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px), succinate dehydrogenase (SDH), nicotinamide adenine dinucleotide (NADH), and citrate synthase (CS) were measured using the corresponding kits (Cat# A003‐1, Cat# A001‐1, Cat# A005, Cat# A022, Cat# A116, and Cat# A108, respectively; Nanjing Jiancheng Bioengineering institute, Nanjing, China), and tissue homogenate protein concentrations were also measured using the BCA kit (Cat# P0010; Beyotime Biotechnology, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The level of these enzymes in the red gastrocnemius was determined as described previously . According to the manufacturer's instructions, the levels of superoxide malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px), succinate dehydrogenase (SDH), nicotinamide adenine dinucleotide (NADH), and citrate synthase (CS) were measured using the corresponding kits (Cat# A003‐1, Cat# A001‐1, Cat# A005, Cat# A022, Cat# A116, and Cat# A108, respectively; Nanjing Jiancheng Bioengineering institute, Nanjing, China), and tissue homogenate protein concentrations were also measured using the BCA kit (Cat# P0010; Beyotime Biotechnology, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed that Gal can protect human keratinocytes against ultraviolet B-induced oxidative damage [25]. In a recent study, Gal has been proven to attenuate liver injury in diabetic rats through maintaining liver mitochondrial function and decreasing oxidative stress [26]. Although several pharmacological actions of Gal have been investigated, nothing is known about its potency to prevent CP-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of galangin to arthritic mice significantly reduced the disease score of arthritis and ameliorated paw oedema and inflammation . Treatment with galangin attenuated hyperglycaemia‐induced elevation of lipid peroxides and elevated reduced glutathione (GSH) levels in a rat model of streptozotocin‐induced diabetes . Galangin treatment was also found to inhibit malondialdehyde (MDA) production and augment the serum‐free radical scavenging capacity .…”
Section: Introductionmentioning
confidence: 99%